Effect of cooling rate to the mechanical properties of polypropylene produced by hot compression machine - Ling, Yih Lii, 1985-; Yob Saed Ismail, supervisor; Fakulti Kejuruteraan Mekanikal (2009)
Project Paper (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2009